Designing a Mobile Application Prototype for Accessing and Publishing Student Journals using Figma - Alda, Muhamad; Kurniawan, Ardi Ari; Ramadhani, Vidya; Ananda, Muhammad Revandy (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2026)
The advancement of digital technology has driven significant changes in academic information management, including student journal publications. This study aims to design a mobile application prototype as a medium for accessing and publishing journals within the Faculty of Science and Technology at the State Islamic University of North Sumatra. The method employed is the prototyping model, which emphasizes an iterative process between designers and users. The research stages include needs identification, initial design creation, evaluation, and design refinement using Figma as an interface design tool. The results of this research demonstrate a prototype application that includes key features such as journal uploading, searching, and downloading of student scientific papers. Initial evaluations reveal that the design is easy to understand, has clear navigation, and meets user needs. Furthermore, application testing shows a significant improvement in the effectiveness of journal publication access for students, as well as ease of managing academic papers in a more structured and systematic way. This prototype is expected to serve as a foundation for the development of a more integrated and efficient student journal repository system in the future. Additionally, this study contributes to the advancement of information technology in the academic context, particularly in faculty and higher education institutions in Indonesia.